PROMOTING PASSION-BASED LEARNING AS A SOLUTION OF IMPROVING CREATIVITY IN ENGLISH CLASSROOM - Mas?ud, Bulqia; Fachruddin, Achmad Taqlidul Chair; Syamsinar, Syamsinar (Inspiring: English Education Journal, 2019)
This article investigates a pedagogical interference in promoting creativity   in  English  classroom  that  describe  the  importance  of  creativity  in  learning process. The article explores the idea of passion-based learning in improving creativity in the classroom specially in English subject. By using secondary data both  from  journals,  books,  and  internet  sites,  researcher  is  able  to  apply descriptive analysis through literary review methods. Promoting passion-based learning might be a possible way to improve creativity in English Classroom. Passion-based learning could be a solution that give ownership and authority to students to explore their own creativity in the classroom hence give them meaningful  learning.  Some  tangible  ways  in  this  article  could  be  applied  by English teachers to create passion-based learning in English classroom that can improve the students? reading, listening, speaking and writing skill and creativity. The emerging challenge found in this study is passion-based learning is difficult to apply in large class since it gives freedom to students choose what they want to learn hence classroom activities will not be feasible to control. Besides, passion- based learning needs creative and skilful teachers to come up with various and interesting ideas to stimulate dynamic in classroom.  Therefore, the quality of teacher is highly considered in applying passion-based learning. Teachers should be expert in subjects they teach. Promoting teacher professional development need to be considered to improve creativity in English classroom with given English teachers? opportunities to explore their potentials.